Purulent pericarditis caused by Nocardia: a case report and literature review - Zhong, Xinxin; Lin, Ao; Cao, Fu; Jiang, Shihao; Ruan, Yuying; Li, Shuting; Zhong, Li; He, Zhiyi; Luo, Jian (Frontiers in Cardiovascular Medicine, 2025)
Purulent pericarditis caused by Nocardia, a rare opportunistic infection associated with a high mortality, is frequently misdiagnosed as Mycobacterium tuberculosis (MTB) or other bacterial infections. We report a case of Nocardia-induced purulent pericarditis in a patient with acquired immune deficiency syndrome (AIDS). The patient experienced multiple misdiagnoses and received inappropriate anti-tuberculosis therapy. Timely pericardial puncture and subsequent culture of the pericardial effusion identified Nocardia, prompting initiation of appropriate antibiotic therapy which led to clinical cure. This case report underscores the importance of broad differential diagnostic considerations in purulent pericarditis and emphasizes that prompt initiation of Nocardia-directed antibiotic therapy, guided by microbiological identification, is crucial for timely diagnosis and management. Additionally, we review and summarize previously reported cases of laboratory-confirmed Nocardia pericarditis in AIDS patients.